Conectivismo: Hacia El Nuevo Paradigma De La Enseñanza Por Competencias - Marisa Cecilia Tumino; Juan Manuel Bournissen (European Scientific Journal, ESJ, 2016)
The three main learning theories most frequently used in the design and creation of instructional environments are behaviorism, cognitivism and constructivism. In the last years, technology has reorganized the way we live, communicate and learn. The arrival of the web 2.0 has greatly increased students’ access to the interconnected information required for their professional formation. Scientific and technological progress has impelled innovation as an assertive paradigm of the well-meant development efforts of a knowledge society in continuous transformation. One of the great challenges faced by educational institutions is that of training competent professionals qualified to adapt themselves to the ceaseless changes and challenges posed by each discipline, with the consequent responsibility of implementing teaching and evaluation techniques which would allow to identify the degree of achievement of professional competencies aimed to develop in the students. This essay addresses the way in which Informatics -as a science which studies methods, processes, and storage, processing and transmission techniquescan lay the foundations this changes convey and introduce innovative practices aimed to get hold of the benefits of connectivism to strengthen competencies of the professional profile. According to Bartolomé (2011), in connectivism -as a learning theory first introduced by Siemens and Downeslearning is produced through a process of connecting and generating information in the context of a learning community, where this community acts as a node, part of a bigger net with other nodes sharing resources with each other. The size and strength of the nodes varies according to the concentration of information and the number of individuals participating in the node. Knowledge is distributed throughout the net. Some interesting concepts are the continuous change of validity and precision of information (knowledge dynamics) and also the change in the students’ skills over time. Drawing from the information gathered in this study, it is believed that the self-determined learning methodology, along with the resources gained through connectivism, creates a beneficial scenario for the professional training aimed to develop the competences demanded by society.